Ketahanan Eksplan Embrio Ayam Dalam Media In Vitro - Atik Kurniawati; Dwi Listyorini (Universitas Muhammadiyah Surakarta, 2021)
Science has implemented the cell cultures as the primary for research such as a model system, toxicity tests, cancer, viruses, cell-based industries, genetic counseling, genetic engineering, gene therapy, drug screening and the latest is invitro meat. The purpose of this study was to determine the resistance of chicken embryo eksplan cells in invitro media. The research design was in the form of laboratory experiments. Explants taken 4 day old chick embryos, which were cultured in MEM media + serum. The results showed fibroblast cell cultures which survive 2 days. The most influential factor is the environment that is less supportive of the growth of explant chicken embryo cell